Pengembangan Lembar Kerja Peserta Didik (LKPD) berbasis potensi lokal pada Materi Fungi untuk siswa Kelas X SMK - Ummi Ummi; Irma Irma; Andi Andi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This study aims to develop learning media in the form of Student Activity Sheet (LKPD) to help the students understand about fungi. This research and development (RnD) study employed ADDIE model. In collecting the data, several techniques were employed such as observation, interviews, and questionnaires. The development phase was carried out by validating the LKPD to two experts. Then, it was implemented in SMK Yapki Pergis Maros in tenth and eleventh grade students majoring Agribusiness and Agrotechnology involving 10 students. The result of practicality tests, which was conducted by the teacher and students on the use of media, showed that 85% of them categorized the LKPD as good/ valid. The results of field trials on the response of teachers and students obtained overall score of 74.29% and the teacher's response and the students' test obtained 81%, both of which are in the category of positive responses. The feasibility assessment which is reviewed based on validity and practicality, it can be concluded that the Student Activity Sheet (LKPD) based on local potential is valid and practical.